An EISCAT UHF/ESR Experiment That Explains How Ionospheric Irregularities Induce GPS Phase Fluctuations at Auroral and Polar Latitudes - John, Habila; Forte, Biagio; Astin, Ivan; Allbrook, T.; Arnold, A.; Vani, Bruno; Häggström, Ingemar; Sato, Hiroatsu (Radio Science, 2021)
A limitation to the use of Global Navigation Satellite System (GNSS) for precise and real-time services is introduced by irregularities in the ionospheric plasma density. An EISCAT UHF/ESR experiment was conducted to characterize the effect of electron density irregularities on temporal fluctuations in TEC along directions transverse to GPS ray paths in the high latitudes ionosphere. Two representative case studies are described: Enhancements in temporal TEC fluctuations originating (a) in the auroral ionosphere following auroral particle precipitation and (b) in the polar ionosphere following the drift of a polar patch as well as particle precipitation. The results indicate that the origin of enhancements in TEC fluctuations is due to the propagation through large-to-medium scale irregularities (i.e., ranging from few kilometres in the E region to few tens of kilometres in the F region) and occurring over spatial distances of up to approximately 400 km in the E region and up to approximately 800 km in the F region with a patchy distribution. Furthermore, the results indicate that enhancements in TEC fluctuations produced by polar plasma patches and particle precipitation occur over similar temporal scales, thus explaining the overall observation of higher phase scintillation indices in the high-latitude ionosphere. The similarity in the temporal scales over which enhancements in TEC fluctuations occur in the presence of both particle precipitation and plasma patches suggests an intrinsic limitation in the monitoring and tracking of plasma patches through ground GNSS observations.